Menyingkap Celah Hukum: Pertanggungjawaban Pidana Notaris dalam Penyalahgunaan Akta Elektronik - Rusmana, I Putu Edi (Acta Comitas; Vol 10 No 01 (2025), 2025)
This study aims sto analyzes the criminal liability of notaries in abuse of authority, especially in the making of electronic deeds which are increasingly relevant in the digital era. Although the development of information technology has facilitated legal services, the potential for abuse such as data manipulation and forgery of deeds remains a serious threat. This study uses a normative method with a legislative approach to examine relevant regulations, such as Law Number 2 of 2014 concerning amendments to Law Number 30 of 2004 concerning the Position of Notary, Law Number 1 of 2024 concerning the second amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions, and the Criminal Code (KUHP). The results of the study show that although there is a legal basis for applying criminal sanctions, regulations related to electronic deeds by notaries still have legal loopholes, especially in supervision and mechanisms for preventing abuse. The novelty in this study lies in the analysis of the effectiveness of the ITE Law update which provides a legal basis for regulating digital aspects in the notary profession.